(untitled) (Bangladesh Agronomy Journal, 2016)
The present piece of research work was carried out at the field of Sher-e-Bangla Agricultural University, Dhaka-1207, from December 2010 to May 2011 to determine optimum irrigation levels for the hybrid maize varieties. There were four hybrid maize varieties: V1 (BARI Hybrid Maize-5), V2 (Pacific 60), V3 (NK 40) and V4 (Ajanta) and three levels of irrigation: I1 = Two irrigations at 25 and 50 DAS, I2 = Three irrigations at 25, 50 and 75 DAS and I3 = Four irrigations at 25, 50, 75 and 100 DAS, respectively. Almost all the plant and yield contributing characters showed significant variation except days to 6 leaf stage and days to bud initiation stage. The maximum yields were recorded in V1I3 (7.92 t ha-1) which was statistically identical to V4I3 (7.83 t ha-1), V2I3 (7.45 t ha-1), V1I2 (7.40 t ha-1), V2I2 (6.87 t ha-1) and V4I2 (6.80 t ha-1), respectively. The highest benefit cost ratio (BCR) was observed (2.37) in both V1I3 and V1I2 treatment combination. Moreover, total average water saving in one hectare land for maize cultivation by adopting I2 irrigation treatment over I3 is 4,49,837 gallons. Among the treatment combinations, V1I3 (BARI Hybrid Maize-5 with three irrigations at 25, 50 and 75 DAS) was the suitable combination in terms of grain yield and economic return for maize cultivation. Bangladesh Agron. J. 2015, 18(2): 23-29